The influence of oil extraction process of different rapeseed varieties on the ileal digestibility of crude protein and amino acids in broiler chickens - Kasprzak, M.M.; Houdijk, J.G.M.; Olukosi, O.A.; Appleyard, H.; Kightley, S.P.J.; Carre, P.; Wiseman, J. (Elsevier Masson, 2017)
The current study assessed the effect of rapeseed variety and oil extraction process on the apparent and standardised ileal digestibility (AID, SID) of crude protein (CP) and amino acids (AA) in rapeseed co-products in broiler chickens. PR46W21 and DK Cabernet rapeseed varieties were de-oiled by soft and standard hexane extraction, producing soft rapeseed meal (SRSM) and rapeseed meal (RSM), respectively. The soft, non-standard hexane extraction method was designed to reduce heat treatment that occurs prior to hexane extraction in order to maximise potential genetic differences in digestibility values of rapeseed co-products. The test meals were incorporated into semi-synthetic diets at a level of 500 g/kg; diets were fed to 14-day old paired chickens (n = 6 pairs) for ten days, when ileal digesta was collected post-slaughter from Meckel’s diverticulum to the ileal-caecal junction. The AID and SID of CP and AA were determined using titanium dioxide as inert dietary marker. The variety PR46W21 showed a greater AID and SID of CP, arginine, leucine, methionine, cysteine, phenylalanine, valine and lysine in RSM compared to the DK Cabernet RSM (p < 0.05). The soft processing increased AID and SID of CP, histidine and lysine in SRSM of PR46W21 and DK Cabernet compared to their RSM counterparts (p < 0.05). An interaction between variety and processing was only observed for AID and SID of tryptophan (p < 0.001), as only in PR46W21 standard processing reduced the tryptophan SID compared to its soft processed counterpart. The data support the view that the selection of rapeseed variety and modification of thermal treatment during the oil extraction might improve nutritional value of rapeseed meals.